Hubungan Self Efficacy dengan Quarter Life Crisis pada Mahasiswa Tingkat Akhir di Universitas Negeri Padang - Juwita Putri Andini; Yolivia Irna Aviani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
With a high level of self-efficacy, students can face quarter-life crisis easily. People who have self-efficacy will focus and do their tasks without any problems in difficult situations. Students who have self-efficacy are more confident and able to reach their full potential. In addition, it helps students acquire the skills needed for future success. The purpose of this study was to empirically investigate the relationship between self-efficacy of final year students at Padang State University and quarter-life crisis. This study combines cluster sampling strategy with quantitative approach. A total of 292 final year students at Padang State University became the research sample. With an error rate of 5%, this sample was taken using Isaac and Michael table. The data analysis method used is Pearson Product Moment. The results showed that quarter-life crisis and self-efficacy of final year students at Padang State University were each in the moderate range with a proportion of self-efficacy of 39.7% and quarter-life crisis of 28.4%. The research hypothesis stating that there is a significant negative relationship between self-efficacy and quarter life crisis in final year students at Padang State University is accepted based on the hypothesis test which produces a value of r = -0.469 with a significance level of p = 0.000 (p < 0.05).